The Effect of Instructor Competence on the Learning Process in the PKW Program in Makassar City - Muhammad Ilham Akbar B; Sucipto Sucipto; Zulkarnain Zulkarnain (Universitas Negeri Padang, 2024)
This study aims to investigate the influence of instructor competency on the learning process in the Entrepreneurial Skills Education Program (PKW). In this research, a quantitative approach was utilized involving 85 respondents who are adult learners who have previously participated in the PKW Program at the Course and Training Institute (LKP) in Makassar City. This study employs hypothesis testing with a simple regression model to examine the impact of variable X, denoted as instructor competency, on variable Y, representing the PKW learning process. The findings reveal a noteworthy association between instructor competency and the PKW learning process, signifying a positive correlation. This suggests that as instructor competency increases, the quality of the PKW learning process improves. Such findings carry significant implications for enhancing the quality of entrepreneurial skills education. Investing in the development of instructor competency can serve as a strategic approach to augmenting the efficacy and efficiency of the learning process.